Diseño de un prototipo didáctico con arduino para la enseñanza de matemática - Medina Puga, Yessenia del Carmen (2025)
Technological teaching resources have a great importance in educational environments and in the performance of teaching work. The objective of this research is to design a didactic prototype with Arduino as a support material for the teaching of matrix operations in educational environments. The study is exploratory with a qualitative approach. The method of bibliographic review was used, applying the fiching technique to organize the information, and the instruments used were the search log, bibliographic and content cards. The results indicate that, in order to teach mathematics effectively, the teacher must have disciplinary, procedural and evaluative knowledge, as well as the use of technological didactic resources as a complement. In conclusion, the process of teaching matrix operations is strengthened when technological didactic resources such as prototypes are used, since it is an effective way to innovate educational practice, because it stimulates curiosity and motivates students to develop mathematical skills and, at the same time, allows the development of constructive and active learning